Identifying Lung Cancer Patients Suitable for Segmentectomy: A Brief Review - Wang, Chunguo; Wu, Sikai; Zhang, Rongwei; Jin, Ke; Qian, Yicheng; Mao, Ning; Liu, Yun; Zhang, Miao; Zhang, Ke; Wang, Renfeng; Huang, Gang; Zhang, Min; et al. (Frontiers in Surgery, 2021)
Background：In 1995, a clinical randomized controlled study (RCT) conducted by the Lung Cancer Study Group (LCSG) pointed out that the lobectomy was the gold standard for treating early lung cancer. However, with the development of technology, the results of several retrospective studies have shown that the efficacy of pulmonary segmentectomy is equivalent to that of lobectomy. At the same time, pulmonary segmentectomy can better preserve the patient's postoperative lung function. Currently, it is still controversial whether segmental resection or lobectomy should be performed for early lung cancer. Thus, we aim to summarize the indications of segmentectomy. Methods：To conduct the review, previous research involving indications of segmentectomy were collected from the literature using Pubmed. These articles were published and accepted in English in the medical literature from 2013 to 2020. We have focused on segmentectomy and its indications. Results：We summarized the indications and criteria for segmentectomy in lung cancer. Some complex anatomy segmentectomies and advanced operating procedures also are included. In addition, the potential and prospect of segmentectomy for the treatment of lung cancer is emphasized. Conclusions：These findings have a number of important implications for future practice. Pulmonary segmentectomy is a very significant surgical procedure for select patients with lung cancer, which provides a novel approach for the treatment of lung cancer and for the survival of lung cancer patients.